PERSEPSI TAMU TERHADAP KUALITAS PELAYANAN HOTEL: STUDI KUALITATIF MENGGUNAKAN METODE SERVQUAL DI HOTEL HARPER KUPANG - Linda Marlince Taka; Habel Ada Koinmanas; Moshe Markhasi Rupilu (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Service quality is a strategic factor in the hotel industry, as it directly influences guest satisfaction, loyalty, and destination image. Harper Kupang Hotel, a star-rated hotel operating in Eastern Indonesia, faces increasing challenges in meeting increasingly complex guest expectations, particularly in the post-pandemic period and amid intensified competition in the hospitality industry. This study aims to examine guest perceptions of service quality at Harper Kupang Hotel through an in-depth qualitative approach using the SERVQUAL framework. The research employed a qualitative case study design, with data collected through in-depth interviews with 15 purposively selected informants, comprising business and leisure guests. Data were analyzed using thematic analysis to identify gaps between expected and perceived service quality across the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that the tangibles and assurance dimensions are perceived relatively positively. At the same time, significant gaps remain in the responsiveness and empathy dimensions, particularly regarding service speed, consistency of service attitudes, and personalization of guest interactions. These results suggest that operational standards do not solely determine service quality but are strongly influenced by employees’ interpersonal competencies and their sensitivity to guest needs. Theoretically, this study reinforces the relevance of SERVQUAL within a qualitative research context and contributes to the literature on hotel service perceptions in marginal tourism regions. In practical terms, the findings offer strategic recommendations for hotel management and regional tourism.